DEVELOPING A TUBERCULOSIS PROTOCOL MANUAL FOR THE SALINE COUNTY HEALTH DEPARTMENT - Yang, Jonathan (My University, 2017)
Tuberculosis (TB) is a communicable disease in humans caused most commonly by Mycobacterium tuberculosis and less commonly by other bacterial species in the Mycobacterium tuberculosis complex (Africanum, bovis, microti, etc.). A strictly followed drug regimen administered by directly observed therapy (DOT) is the standard of treating TB, due to the severity of consequences of treatment non-compliance (e.g. acquired drug resistance). Prevention and management of TB is best done by targeted testing of at-risk populations, management and treatment of both latent and active TB cases, contact investigations of cases, and properly applied infection control methods. The Kansas Tuberculosis Control Program (founded 1901) currently supports local public health agencies, physicians, and health care facilities responsible for TB control and management, and provides medications for nearly 90% of Kansas TB cases. However, the program does not provide a structured guide for TB management and control, and health care workers rely on outside source manuals for referral during TB care. In the event of a TB outbreak, it is critical that clear and concise health communication is exchanged between the health care workers who administer DOT and the TB patients. Therefore, as the fieldwork’s primary objective, a TB protocol manual was developed, using adapted literature review, to cater to the Saline County Health Department’s Communicable Disease/TB Program and other local Kansan health departments if they choose to adopt the manual. Comprised in this report are the learning objectives and competencies required for the culminating experience, all relevant data visualizations and analyses, and the document produced (SCHD Guidelines for the Prevention, Diagnosis, and Treatment of Tuberculosis 2017), completed in partial fulfillment of the requirements for the Master of Public Health degree from Kansas State University. The field experience was conducted at the Saline County Health Department, a county-level health agency serving the residents of Salina and several neighboring communities.
Keywords: TB; mycobacterium; Tuberculosis Prevention; Tuberculosis Diagnosis; Tuberculosis Treatment